Influence of silicon on growth mechanism of micro-arc oxidation coating on cast Al–Si alloy - Huijun Yu; Qing Dong; Yang Chen; Chuanzhong Chen (Royal Society Open Science, 2018)
Micro-arc oxidation (MAO) is a plasma-assisted electrochemistry method to prepare protective ceramic coatings on aluminium alloys. Alloy elements of the Al-alloy substrate, such as Si, Cu, Mg and Li, have effects on the microstructure and composition of the MAO coatings. Usually, silicon distributes in the cast Al–Si alloy substrate as small laths and they cover approximately 10% of the substrate surface. Therefore, their effects on the growth process and microstructure of the MAO coatings are worthy of notice. In the present study, oxide coatings with a thickness of 15–18 µm were prepared on the ZL109 Al–Si alloy by MAO. The phase content, surface morphology and element distribution of the coatings were investigated by X-ray diffraction, grazing incidence X-ray diffraction, scanning electron microscope, and electron probe micro-analysis respectively. The average hardness of the coatings was 622.3 ± 10.2 HV0.05. The adhesive strength of the coatings is 40.55 ± 2.55 N, and the adhesion of the coatings could be rated as 5B by tape test according to ASTM D3359-17 standard test methods, which indicated a high adhesive strength between the MAO coating and substrate. The effects of silicon laths on surface morphology and composition of the coatings were discussed, and a model was put forward to describe the growth process of the MAO coatings on cast Al–Si alloys. The authors believe that the high silicon content of the substrate has no adverse influence on the structure and properties of the MAO coating on the ZL109 alloy.